A STUDY ON EMOTIONAL INTELLIGENCE AND ADJUSTMENT OF SECONDARY SCHOOL STUDENTS - Arya, Mohan Lal (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The present study has been designed to study the Emotional Intelligence among Sr. Sec. School Students in relation to their Gender and Type of School. For this purpose a sample of 640 Secondary School Students, selected randomly from secondary schools of Moradabad district. All the secondary school students in Moradabad district govt. /private schools, as well as male/female students made up the population of the study. Data was collected by Self developed tool of Emotional Intelligence and adjustment scale by A. K. P. Sinha and R. P. Singh. The result revealed that there is significant difference in emotional intelligence and adjustment of Secondary school students with respect to nature of the school and there is no significant difference in emotional intelligence and adjustment of Secondary school students with respect to gender. Significant correlation was found between emotional intelligence and adjustment among Sr. Sec.School Students.